2012
DOI: 10.1186/1471-2377-12-124
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and fetal outcomes after Glatiramer Acetate exposure in patients with multiple sclerosis: a prospective observational multicentric study

Abstract: BackgroundOnly few studies have assessed safety of in utero exposure to glatiramer acetate (GA). Following a previous study assessing the safety of interferon beta (IFNB) pregnancy exposure in multiple sclerosis (MS), we aimed to assess pregnancy and fetal outcomes after in utero exposure to GA, using the same dataset, with a specific focus on the risk of spontaneous abortion.Materials and methodsWe recruited MS patients, prospectively followed-up in 21 Italian MS Centres, for whom a pregnancy was recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 15 publications
4
61
1
3
Order By: Relevance
“…Considering the choice among first-line therapies, GA offers an obvious advantage in young, potentially fertile women for the favourable safety profile in this population, as discussed above [107]. Patients with CIS are also expected to benefit from GA, given the evidence of efficacy in such patients, supported by extension studies showing clear protection from brain atrophy [86,87].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Considering the choice among first-line therapies, GA offers an obvious advantage in young, potentially fertile women for the favourable safety profile in this population, as discussed above [107]. Patients with CIS are also expected to benefit from GA, given the evidence of efficacy in such patients, supported by extension studies showing clear protection from brain atrophy [86,87].…”
Section: Discussionmentioning
confidence: 97%
“…An Italian retrospective study showed that the mother's exposure to GA when the drug was suspended within 4 weeks from conception was not associated with an increased frequency of spontaneous abortion nor with other negative pregnancy and foetal outcomes compared with women in whom the medication was suspended 4 weeks or more from conception, or who were untreated [107]. These findings confirm those of a previous observational study [106] suggesting that GA and the IFNs do not represent a significant risk for prenatal developmental toxicity.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy loss not observed (n = 31 [13], n = 46 [61] and n = 17 [62]) Decreased fetal growth not observed (n = 31 [13] and n = 17 [62]) Teratogenicity not observed (n = 31 [13], n = 46 [61] and n = 17 [62]) Impaired development of the newborn not observed (n = 11 [16] Recommend discontinuation prior to conception or once pregnancy is known [7,8] with some suggesting a washout period of at least 1 month prior to conception [60] for women with mild MS Use until conception or into pregnancy may be recommended for women with severe or highly active MS [6] Use not recommended in breastfeeding [6] Natalizumab Contraception required for women with childbearing potential; recommend discontinuation at least 3 months prior to conception [6] Use not recommended in breastfeeding [6,11] MS: Multiple sclerosis.…”
Section: Special Reportmentioning
confidence: 99%
“…Although safety data on exposure for newer drugs like natalizumab and fingolimod are still lacking 9 , there seems to be strong data on the safety of glatiramer acetate 10,11 and interferon beta 11,12 exposure during pregnancy. Is it time to rethink our recommendations?…”
mentioning
confidence: 99%